Massive Plexiform Neurofibroma of the Neck and Larynx - Mobashir,Mohammad Kamal (2015)
Introduction Laryngeal neurofibromas are extremely rare, accounting for only 0.03 to 0.1% of benign tumors of the larynx. Objectives To report the first case of massive neck plexiform neurofibroma with intralaryngeal (supraglottic) extension in a 5-year-old boy with neurofibromatosis type 1 and to describe its treatment. Resumed Report This massive plexiform neurofibroma was surgically removed, relieving its significant respiratory obstructive symptoms without recurrence to date. Conclusion Massive neck plexiform neurofibroma with supraglottic part was found in a child with neurofibromatosis type 1; it should be included in differential diagnosis of stridor and neck mass in children. It was diagnosed and removed in early in childhood without recurrence.